Biologic drugs in the treatment of chronic inflammatory pulmonary diseases: recent developments and future perspectives - Plichta, Jacek; Kuna, Piotr; Panek, Michał (Frontiers in Immunology, 2023)
Chronic inflammatory diseases of the lung are some of the leading causes of mortality and significant morbidity worldwide. Despite the tremendous burden these conditions put on global healthcare, treatment options for most of these diseases remain scarce. Inhaled corticosteroids and beta adrenergic agonists, while effective for symptom control and widely available, are linked to severe and progressive side effects, affecting long-term patient compliance. Biologic drugs, in particular peptide inhibitors and monoclonal antibodies show promise as therapeutics for chronic pulmonary diseases. Peptide inhibitor-based treatments have already been proposed for a range of diseases, including infectious disease, cancers and even Alzheimer disease, while monoclonal antibodies have already been implemented as therapeutics for a range of conditions. A number of biologic agents are currently being developed for the treatment of asthma, chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis and pulmonary sarcoidosis. This article is a review of the biologics already employed in the treatment of chronic inflammatory pulmonary diseases and recent progress in the development of the most promising of those treatments, with particular focus on randomised clinical trial outcomes.